Mineralogical signature of hydrocarbon circulation in Cretaceous red beds of the Barda González area, Neuquén Basin, Argentina - Pons, María Josefina (2015)
The Portezuelo Formation is part of a red bed sequence in the Neuquén Basin assigned to the Neuquén Group (Lower Cenomanian-Middle Campanian). In outcrops of the Portezuelo Formation in the Barda González region, iron oxide and hydroxide cements are only preserved in the less permeable claystone layers. Paleo-migration of hydrocarbons and formation waters along the most permeable layers bleached the rocks due to partial- to total dissolution of cements and grains and formation of several authigenic minerals: 1) montmorillonite and pyrite in the medium- to fine-grained sandstones and mudstones, and 2) multi-stage calcite and pyrite in the coarse-grained sandstones and conglomerates.The δ34SCDT of -24.4 to -60? values in pyrite point to microbial reduction of a sulfate precursor. The oxidation of hydrocarbons and fluctuations in pH and PCO2 caused by organic acids resulted in multiple stages of dissolution and precipitation of calcite. Calcite crystals host hydrocarbon-bearing fluid inclusions (± pyrite) with variable fluorescence colour, indicating that hydrocarbon composition changed with time. The intermediate δ13CPDB (−8.11? to −8.52?) and δ18OPDB (−9.76 to −9.87?) isotope composition of calcites may have resulted from mixtures of 13C-rich CO2 after the dissolution of local calcrete with 13C-poor CO2 from oxidizing hydrocarbons. This contribution provides for the first time key information to predict the distribution of authigenic minerals in reservoir rocks in the basin and improves understanding of the diagenetic history of the Portezuelo Formation.